Pengaruh Literasi Keuangan Terhadap Minat Berinvestasi Saham Pada Mahasiswa - Dwi Pertiwi Anggraini; Suginam Suginam; Joli Afriany; Maringan Sianturi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
Investment is often interpreted as an activity of setting aside some funds to be placed in investment vehicles with the hope of reaping economic value in the future. Lack of knowledge about stocks in students also causes a lack of interest in investing. The purpose of this study is to determine the effect of financial literacy on the interest in investing in stocks in students. The population in this study were all students of the Faculty of Economics and Business, Budi Darma University with a sample of 16 students who were taken randomly. The data collection technique in this study was to use a questionnaire. And the data analysis technique used by doing a simple regression analysis. The results of this study partially state that financial literacy has a positive and significant effect on the interest in investing in students. It can be seen that the tcount value for the financial literacy variable is 3,386 > ttable 1,761 and a significant value of 0.005 <0.05, then Ho is rejected and Ha is accepted.